Taming complexity in nonlinear dynamical systems by recycled signal - Sun, ZhongKui; Yang, XiaoLi; Xu, Wei (Science China. Technological sciences, 2016)
In this paper, the impacts of the recycled signal on the dynamic complexity have been studied theoretically and numerically xn a prototypical nonlinear dynamical system. The Melnikov theory is employed to determine the critical boundary, and the sta- tistical complexity measure （SCM） is defined and calculated to quantify the dynamic complexity. It has been found that one can switch the dynamics from the periodic motion to a chaotic one or suppress the chaotic behavior to a periodic one, merely via adjusting the time delay or the amplitude of the recycled signal, therefore, providing a candidate to tame the dynamic com- plexity in nonlinear dynamical systems.